Piezoresistance Characterization of Silicon Nanowires in Uniaxial and Isostatic Pressure Variation - Elham Fakhri; Rodica Plugaru; Muhammad Taha Sultan; Thorsteinn Hanning Kristinsson; Hákon Örn Árnason; Neculai Plugaru; Andrei Manolescu; Snorri Ingvarsson; Halldor Gudfinnur Svavarsson (Sensors, 2022)
Silicon nanowires (SiNWs) are known to exhibit a large piezoresistance (PZR) effect, making them suitable for various sensing applications. Here, we report the results of a PZR investigation on randomly distributed and interconnected vertical silicon nanowire arrays as a pressure sensor. The samples were produced from p-type (100) Si wafers using a silver catalyzed top-down etching process. The piezoresistance response of these SiNW arrays was analyzed by measuring their I-V characteristics under applied uniaxial as well as isostatic pressure. The interconnected SiNWs exhibit increased mechanical stability in comparison with separated or periodic nanowires. The repeatability of the fabrication process and statistical distribution of measurements were also tested on several samples from different batches. A sensing resolution down to roughly 1<semantics>m</semantics> pressure was observed with uniaxial force application, and more than two orders of magnitude resistance variation were determined for isostatic pressure below atmospheric pressure.